2013
DOI: 10.1186/1471-2431-13-165
|View full text |Cite
|
Sign up to set email alerts
|

Exogenous surfactant therapy in 2013: what is next? who, when and how should we treat newborn infants in the future?

Abstract: BackgroundSurfactant therapy is one of the few treatments that have dramatically changed clinical practice in neonatology. In addition to respiratory distress syndrome (RDS), surfactant deficiency is observed in many other clinical situations in term and preterm infants, raising several questions regarding the use of surfactant therapy.ObjectivesThis review focuses on several points of interest, including some controversial or confusing topics being faced by clinicians together with emerging or innovative conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
17
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 104 publications
3
17
0
2
Order By: Relevance
“…Infants were not offered intensive care due to limited resources, either because of lack of bed availability or inadequate parental finances. Their unit protocols included most of the newer evidenced-based therapies for this population, including early CPAP, rescue surfactant, and early trophic feedings [2,3].…”
mentioning
confidence: 99%
“…Infants were not offered intensive care due to limited resources, either because of lack of bed availability or inadequate parental finances. Their unit protocols included most of the newer evidenced-based therapies for this population, including early CPAP, rescue surfactant, and early trophic feedings [2,3].…”
mentioning
confidence: 99%
“…Prophylactic use in infants younger than 28 weeks gestation has been shown to decrease short term ventilatory needs but no decrease in incidence of chronic lung disease (BPD) has been proven. 3 The incidence of RDS in preterm infants has been significantly reduced with the use of antenatal steroids that promote lung maturity. The use of antenatal steroids has also been linked to a reduction in the incidence of clinically significant patent ductus arteriosus (PDA) and severe intra ventricular haemorrhage (IVH).…”
mentioning
confidence: 99%
“…Although we found a more recent paper (2013) discussing "exogenous surfactant therapy," it focused primarily on the appropriate timing and methods of administration of surfactant for RDS in preterm infants. 8 Furthermore, although non-RDS conditions were included, the emphasis of the review was not a critical evaluation of the current evidence addressing the use of surfactant for these conditions, but rather, a general overview of potential applications of surfactant therapy outside of RDS. 8 This review presents the evidence and indications for surfactant replacement therapy reported in the literature for non-RDS conditions in the human neonate, focusing primarily on reports published within the last 5 years.…”
mentioning
confidence: 99%